Dynamic triggering of microseismicity in Southwest China following the 2004 Sumatra and 2012 Indian Ocean earthquakes. (1st June 2019) - Li, Lu; Wang, Baoshan; Peng, Zhigang; Li, Danning
Highlights: Clear dynamic triggering is found in SW China after the 2004 Sumatra mainshock. Lack of instantaneous triggering in SW China after the 2012 Indian Ocean mainshock. Minor delayed triggering in Tengchong volcanic field after the 2012 mainshock. Dynamic triggering in a shale gas development region after the 2012 mainshock. The absolute value of dynamic stress is the key factor to different triggering. Abstract: We conduct a systematic detection of microseismicity around Yunnan Province, Southwest China following the 2004 Mw9.1 Sumatra and 2012 Mw8.6 Indian Ocean earthquakes. Based on seismicity analysis on China Earthquake Network Center (CENC) catalog and spectral analysis of continuous waveforms, we find clear evidence of triggered seismicity in Yunnan immediately after the 2004 mainshock, including a magnitude 4.8 earthquake near Tengchong volcanic region. In comparison, we do not find clear evidence of instantaneous triggering following the 2012 mainshock. We further apply a matched filter technique to detect microearthquakes in Tengchong volcanic region 15 days before and 15 days after the 2012 mainshock. The seismicity rate remains stable immediately after the 2012 mainshock, and increases in the next few days, indicating a possible delayed triggering, although similar changes can be seen at other times long before and after the mainshock. In addition, we find possible evidence of remote triggering near the city of Yibin in Southern Sichuan Province, Southwest China, near the sites with ongoing shale gas development. We also examine other magnitude >8 earthquakes from the Sumatra region and do not find any additional evidence of dynamic triggering around Yunnan. We suggest that the absolute value of dynamic stress change is the most important factor to explain why the 2004 Sumatra event triggered a widespread seismicity rate increase around Yunnan, while other great events around Sumatra did not.